Ethnochemistry: Exploring the Potential of Samawa Local Wisdom as a Source for Learning Chemistry - Yeni Cahyani; Dwi Wahyudiati (Hydrogen: Jurnal Kependidikan Kimia, 2023)
One problem in chemistry learning at the secondary and tertiary levels is the availability of appropriate learning resources. To address this problem, it needs contextual teaching materials to implement an ethnochemistry learning approach. This research aims to explore and develop the traditional potential of Samawa local wisdom as chemistry learning material. In addition, this study also explored resources that can be used in teaching chemistry. This qualitative research utilized literature studies, interviews, and documentation to collect the data and was analyzed using Miles & Huberman’s qualitative analysis. As for the sample used in this study were 10th grade students of SMAN 2 Taliwang. I use 2 classes, 1 class as the control class and 1 class as the experimental class.The community leaders, chemistry content experts, and relevant chemistry literature were selected as the study subject. Based on the findings, it can be concluded that Samawa’s local wisdom can be used as a source of chemistry learning through integration with Samawa culture on chemical bonding material. Therefore, this research is expected to be a reference in developing contextual chemistry teaching to create more significant and exciting learning since it is relevant to real-life experience.